2005
DOI: 10.1002/jsfa.2165
|View full text |Cite
|
Sign up to set email alerts
|

Influence of free‐air CO2 enrichment (FACE) on the eating quality of rice

Abstract: Rice plants (Oryza sativa L cv Akitakomachi) were grown under free-air CO 2 enrichment (FACE) in farmers' fields in Shizukuishi, Iwate, Japan during 1999 and 2000. The grains were harvested and subsequently analyzed for protein and amylose contents as well as the traits related to cooked-rice viscosity. The cooked rice was also subjected to sensory evaluation. The protein content of rice grains grown under elevated CO 2 was significantly lower than that of rice grown under ambient conditions. In addition, CO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 22 publications
3
44
0
Order By: Relevance
“…Seneweera et al (1994) reported CO 2 induced increase in amylose content in grains, under various levels of phosphorus application. However, Terao et al (2005) did not observe any change in the palatability of rice grains with the reduction in the protein content under elevated CO 2 condition. Seneweera et al (1994) observed 4% increase of amylose content due to elevated CO 2 under phosphorusdeficient conditions, which is much higher than the decrease in protein content that was less than 2.5%.…”
Section: Ricementioning
confidence: 61%
See 2 more Smart Citations
“…Seneweera et al (1994) reported CO 2 induced increase in amylose content in grains, under various levels of phosphorus application. However, Terao et al (2005) did not observe any change in the palatability of rice grains with the reduction in the protein content under elevated CO 2 condition. Seneweera et al (1994) observed 4% increase of amylose content due to elevated CO 2 under phosphorusdeficient conditions, which is much higher than the decrease in protein content that was less than 2.5%.…”
Section: Ricementioning
confidence: 61%
“…This increase in amylose content was not simply because of the decreased protein content, but also because of the change in the starch composition. Terao et al (2005) also reported that CO 2 enrichment changed the starch pasting properties affecting the texture and stickiness of cooked rice. However, CO 2 induced change in the amylose content did not affect the viscosity of starch.…”
Section: Ricementioning
confidence: 94%
See 1 more Smart Citation
“…In general, the projected increases in [CO 2 ] will promote photosynthesis and crop productivity in the future (Ziska et al, 2012;Tausz et al, 2013). On the other hand, elevated [CO 2 ] (E-[CO 2 ]) is known to reduce the protein content in rice grains (Lieffering et al, 2004;Terao et al, 2005;Taub et al, 2008;Myers et al, 2014), and also degrades grain appearance quality with increased occurrence of chalky grains which will affect the rice market price as well as the nutrient intake of hundreds of millions of people (Borrell et al, 1999). The mechanisms underlying the quality degradation are not well understood, however.…”
Section: Introductionmentioning
confidence: 99%
“…At elevated carbon dioxide and standard fertilizer levels, wheat had 10% less grain protein (Fangmeier et al 1999;Kimball et al 2001). Similarly, grain protein in rice (Terao et al 2005) and tuber nitrogen in potato (Fangmeier et al 2002) declined by about 10% at elevated carbon dioxide concentrations. Several approaches could mitigate these declines in food quality under carbon dioxide enrichment.…”
Section: Carbon Dioxide and Food Qualitymentioning
confidence: 99%